Writing sociology at the beginning of the twenty-first century - Graça, João Carlos (2012)
Paul Veyne has suggested in 1971 that Sociology lacked a study object. Three quarters of a century after Durkheim’s Rules, it had yet to discover social types and orders of preponderant facts. At any rate, Veyne claimed, since Sociology or at least sociologists exist, we must conclude that, under that label, they do something else. Briefly, besides studying the logical conditions of Sociology, we should also sociologically consider it, as well as other neighbour and potentially rival disciplines. In this paper it is argued that, contrary to other scientific fields, Sociology lives in an environment of permanently renewed crisis. Different authors and traditions have indeed asserted exactly that, while based on entirely diverse assumptions. In order to justify the characteristic traits of today’s crisis, we try to list some of the little demons that have contributed to the current situation: 1) The hagiographic syndrome; 2) The isomorphism defence; 3) The acceptance urge.